2010
DOI: 10.5194/angeo-28-1141-2010
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary shock transmitted into the Earth's magnetosheath: Cluster and Double Star observations

Abstract: Abstract. On day 7 May 2005, the plasma instruments on board Double Star TC1 and Cluster SC3 spacecraft register inside the magnetosheath, at 19:15:12 and 19:16:20 UT, respectively, a strong pressure pulse due to the impact of an interplanetary shock wave (IS) on the terrestrial bow shock. The analysis of this event provides clear and quantitative evidences confirming and strengthening some results given by past simulations and observational studies. In fact, here we show that the transmitted shock is slowed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
3
23
3
Order By: Relevance
“…The observed changes of parameters are determined mainly variations through the tangential or compound discontinuity. This numerical prediction is confirmed by recent observations [ Pallocchia et al ., ; Pallocchia , ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed changes of parameters are determined mainly variations through the tangential or compound discontinuity. This numerical prediction is confirmed by recent observations [ Pallocchia et al ., ; Pallocchia , ].…”
Section: Discussionmentioning
confidence: 99%
“…A very similar discontinuity which moves earthward through the magnetosheath has been observed in Cluster data by Pallocchia et al . [] and Pallocchia [] and simulated using the local 3‐D magnetosheath model [ Pallocchia et al ., ]. According to the observations, this discontinuity propagates with the local flow velocity, similar to a tangential discontinuity.…”
Section: Secondary Waves and Discontinuities In Magnetosheathmentioning
confidence: 99%
“…Previous work gives heliosheath speeds for these pressure pulses that range from a dramatic slowing at the termination shock (Zank & Muller 2003) to a small decrease in speed (Steinolfson & Gurnett 1995;Washimi et al 2012;Zank 2015). Studies of solar wind shocks hitting Earth's bow shock suggest that the propagation speed through Earth's magnetosheath is 0.7-1 times the upstream shock speed (Szabo et al 2003;Koval et al 2006;Pallocchia et al 2010). Based on Earth observations and heliosheath models, for a 400 km s −1 upstream speed the heliosheath shock speed is probably 280-400 km s −1 .…”
Section: V2 Mirs and V1 Observationsmentioning
confidence: 99%
“…Global MHD simulations showed ) that a moderately strong interplanetary fast shock, interacting with the Earth's magnetosphere, will be reflected from the ionosphere. The passage of the inbound transmitted shock causes the bow shock and the magnetopause to move inward, while the passage of the sunward-propagating reflected shock causes the boundaries to move out, as confirmed by Pallocchia et al (2010) based on observations aboard Double Star TC1 and Cluster 3. Safrankova et al (2007) suggested that the combination of the inward and outward motions of the bow shock, caused by the transition of an interplanetary shock, results in an indentation of the bow shock surface which flows along the bow shock together with the interplanetary shock.…”
Section: Discussionmentioning
confidence: 65%